Synergic Exfoliation of Graphene with Organic Molecules and Inorganic Ions for the Electrochemical Production of Flexible Electrodes. Issue 3 (29th January 2014) - Xia, Zhen Yuan; Giambastiani, Giuliano; Christodoulou, Christos; Nardi, Marco V.; Koch, Norbert; Treossi, Emanuele; Bellani, Vittorio; Pezzini, Sergio; Corticelli, Franco; Morandi, Vittorio; Zanelli, Alberto; Palermo, Vincenzo
Abstract A facile and efficient method based on electrochemistry for the production of graphene‐based materials for electronics is demonstrated. Uncharged acetonitrile molecules are intercalated in graphite by electrochemical treatment, owing to the synergic action of perchlorate ions dissolved in acetonitrile. Then, acetonitrile molecules are decomposed with microwave irradiation, which causes gas production and rapid graphite exfoliation, with an increase in the graphite volume of up to 600 %. Upon further processing and purification, highly dispersible nanosheets are obtained that can be processed into thin layers by roll‐to‐roll transfer or into thicker electrodes with excellent capacitance stability upon extensive charging/discharging cycles. The good exfoliation yield (>50 % of monolayers), minimal oxidation damage and good electrochemical stability of the nanosheets obtained were confirmed by scanning force and electron microscopy, as well as Raman spectroscopy and galvanostatic analyses.